The role of resilience, positive/negative emotions, and character strengths in predicting burnout of military personnel - Seyed Teymur Seyedi Asl; Amir Mohsen Rahnejat; Mohammad Mehdi Elikaee; Mojgan Khademi; Haleh Shahed-HaghGhadam; Arsia Taghva (فصلنامه ابن سینا, 2020)
Background: Military personnel are at high risk for burnout due to exposure to high job stress. The purpose of this study was to investigate the role of character strengths, positive and negative emotions, and resilience in predicting burnout of military personnel in Iran. Materials and methods: A sample of 146 people working in different military and law enforcement forces was selected by available sampling method. They responded to the Maslach Burnout Inventory (MBI), Stress Questionnaire Conner-Davidson Resilience Scale (CD-RIS), Values in Action Inventory of Strengths (VIA-IS), and Positive and Negative Affect Scale (PANAS). The data were analyzed using descriptive statistics, Pearson correlation coefficient, and stepwise regression. Results: The results showed that job burnout had a negative and significant correlation with resiliency, positive emotions, and all subscales of character strengths (p<0.01). On the other hand, the results of stepwise regression analysis showed that three variables of wisdom and knowledge, courage, and positive emotions can significantly predict burnout (AdjR2 = 0.58 and p<0.001). Conclusion: In conclusion, it seems that positive emotions and some aspects of character strengths can predict occupational burnout. Therefore, these variables can be considered in the selection of military personnel and training after their selection in order to reduce the burnout in them.